2002
DOI: 10.1097/00000658-200201000-00007
|View full text |Cite
|
Sign up to set email alerts
|

p16INK4a is a Prognostic Marker in Resected Ductal Pancreatic Cancer

Abstract: The presence of p16INK4a alterations in resected tumors of patients with PC is connected with a worse prognosis, indicating patients that might benefit from adjuvant therapy regimens. p53 alterations, MDM2 overexpression, and loss of Rb expression could not be identified as prognostic markers from this study, but a larger study with greater statistical power might show a different result with regard to p53.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
4
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 38 publications
5
49
4
1
Order By: Relevance
“…We believe that the significantly larger number of tumors in the current series, 77 tumor samples from 64 patients, provided superior statistical power to demonstrate progressive loss of p16 with tumor progression, unlike previous reports [5]. Similar to pancreatico-biliary [25,26], hepatocellular [27], colorectal [28], and non-small cell lung carcinomas [29], we found that MM that retained p16 expression had longer overall and disease specific survival but this did not reach significance.…”
Section: Discussioncontrasting
confidence: 69%
“…We believe that the significantly larger number of tumors in the current series, 77 tumor samples from 64 patients, provided superior statistical power to demonstrate progressive loss of p16 with tumor progression, unlike previous reports [5]. Similar to pancreatico-biliary [25,26], hepatocellular [27], colorectal [28], and non-small cell lung carcinomas [29], we found that MM that retained p16 expression had longer overall and disease specific survival but this did not reach significance.…”
Section: Discussioncontrasting
confidence: 69%
“…5,6 Moreover, recent studies have extensively demonstrated that the inactivation of p16 INK4A in the members of the INK4 family leads to the development and aggression of a number of human malignancies including HCC. [7][8][9][10][11] These previous studies suggested that the other INK4 family might also play a role in the progression and prognosis of human cancers. Recently, inactivation of p18 INK4C has been reported in various human cancers.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, the loss of p16 expression was detected in 32 of 51 (62.7%) patients with gallbladder cancer. In addition, the loss of p16 expression has been correlated with tumor progression or with decreased survival among patients with carcinoma of the lung, pancreas and esophagus, and malignant melanoma [21,22,24] . The correlation between p16 expression and clinicopathological factors is controversial.…”
Section: Discussionmentioning
confidence: 99%